EVALUATION OF THE CIPP MODEL HOMESCHOOLING PROGRAM PKBM BINA CIPTA UJUNGBERUNG ON PROGRAM EFFECTIVENESS IN UPHOLDING LEARNING QUALITY - Falah, Thufail Ammar; Sukmana, Cucu (IKIP Siliwangi Bandung, 2025)
Homeschooling learning is a program created by PKBM to support the learning needs of participants so that participants who cannot enter the general learning schedule can be replaced with a Homeschooling learning schedule. Testing is needed in the form of evaluation to measure how far the program is running well and in accordance with the objectives. beginning. The implementation method is carried out by observing. The Homeschooling Program has an assessment of 15 points which is categorized as positive and 1 point which is categorized as medium. Apart from that, there are assessment guidelines for observations on the quality of facilities and infrastructure with 3 (very good) and monitoring and evaluation with 2 points (very good) and 1 point (good). It was concluded that the Homeschooling program was running well